The production ability of rabbit does in relation to their longevity - Szendrő, Zsolt; Biróné Németh, Edit; Radnai, István; Milisits, Gábor; Zimányi, A. (Acta Agraria Kaposváriensis, 1998)
197 Pannon White does were divided into groups based on the total number of litters they had had (A = 1–3, B = 4–6, C = 7–9, D = over 9) and the length of time spent in production (below 0.5, 0.5–1, 1–1.5, 1.5–2 and over 2 years). It was established that the does performing above average at early age remained productive for a longer time. The authors are of the opinion that performance at early age gives indications of the animal’s constitution. The constitutionally better and healthier does usually have a longer productive life.